Perkembangan Peserta didik SMA (Sekolah Menengah Atas) - Khoirul Umam Addzaky (JURNAL ILMIAH NUSANTARA, 2024)
This research aims to explore in depth the various aspects of high school students' development, including physical, cognitive, creativity, personal, self-conception, independence, resilience, interpersonal relationships, moral, and spiritual. The method used is a systematic literature review from various trusted academic sources. The discussion shows that the development of high school students is multidimensional and influenced by complex interactions between genetic and environmental factors. They experience significant changes in these aspects, along with challenges such as academic pressure, interpersonal conflicts, and mental health problems. Appropriate support and guidance from the surrounding environment is necessary to facilitate healthy and optimal growth. This study provides insights for the development of education, guidance, and counseling programs that are appropriate to the developmental stages of high school learners.